Both source‐ and recipient‐range phylogenetic community structure can predict the outcome of avian introductions. Issue 2 (24th December 2021) - Maitner, Brian S.; Park, Daniel S.; Enquist, Brian J.; Dlugosch, Katrina M.
Abstract : Competing phylogenetic models have been proposed to explain the success of species introduced to other communities. Here, we present a study predicting the establishment success of birds introduced to Florida, Hawaii and New Zealand using several alternative models, considering species' phylogenetic relatedness to source‐ and recipient‐range taxa, propagule pressure and traits. We find consistent support for the predictive ability of source‐region phylogenetic structure. However, we find that the effects of recipient‐region phylogenetic structure vary in sign and magnitude depending on inclusion of source‐region phylogenetic structure, delineation of the recipient species pool and the use of phylogenetic correction in the models. We argue that tests of alternative phylogenetic hypotheses including both source and recipient community phylogenetic structure, as well as important covariates such as propagule pressure, are likely to be critical for identifying general phylogenetic patterns in introduction success, predicting future invasions and for stimulating further exploration of the underlying mechanisms of invasibility.